Industrial training report: UiTM Puncak Alam / Elyn Fardyana Mohammad Noor Azam - Mohammad Noor Azam, Elyn Fardyana (Perpustakaan Tengku Anis, 2017)
This industrial training report consists of four (4) chapters and that are the introduction, background of organization, industrial training activities and conclusion. Chapter 1 is the introduction on what is actually industrial training was, Chapter 2 is about the background and hist01y of the organization, Chapter 3 is basically about all the activities that I've done during the industrial training period and lastly, the conclusion and outcome that I get during the training. In order to complete my study, I need to undergo 5 months of practical training in industly starting from 1st of February 2017 until 30th of June 2017. The organization that has been selected was the University Mara of Technology (UiTM) Puncak Alam Campus. I was put under the Information and Communications Technology (JCT) Department in Administration Unit. Training schedule has been prepared by the organization supervisor for me to learn the important task in documentation in JCT field. Besides that, I also get to learn how to improve my communication skills, learn to be more discipline and punctual. Last but not least, the knowledge, skills and experience gain during the training is the best method for me to prepare and expose me to the real working environment and also to be good in the future.